Integrasi Epistemologi (Bayani, Burhani, dan Irfani) Dalam Pendidikan Islam Kontemporer - Erdiyani, Fenny; Syarif, Zainuddin; Inayati, Mahfida; Fitriyah, Eliyatul (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the integrative relationship between the epistemological frameworks of Bayani, Burhani, and Irfani and their relevance to contemporary Islamic education. The research addresses the limited implementation of integrative epistemology in Islamic educational institutions, which tend to apply these epistemic models partially. Using a qualitative library research design, this study employs content analysis to examine primary texts from M. Amin Abdullah, Suhrawardi, and Mulla Sadra, supported by secondary literature from scholarly works and journals. The findings reveal that dominance of a single epistemology particularly Bayani creates an imbalance that marginalizes rational and spiritual dimensions. The study identifies that an integrative-interconnective model enables a more holistic educational paradigm by harmonizing textual authority, rational inquiry, and spiritual intuition. This integrated approach is proven capable of strengthening curriculum development, enriching pedagogical practices, and enhancing students’ character formation in contemporary Islamic education. The study concludes that adopting an integrative epistemological model is crucial for developing an Islamic education system that is responsive, balanced, and aligned with modern scientific developments.